PANTANG PULANG SEBELUM PADAM: DISIPLIN, TEAMWORK, MOTIVASI DAN KINERJA PETUGAS PEMADAM KEBAKARAN - Khofifah , Nisa' Nur; Firdaus , Vera; Sumartik , Sumartik (Universitas Bina Taruna Gorontalo, 2025)
This study aims to examine the relationship between work discipline, teamwork, and work motivation in shaping the performance of firefighters with the spirit of not going home before the fire is out. This research employs a descriptive quantitative method. The number of respondents in this study was 107 firefighters. Primary data was collected through a survey using a questionnaire, measured with a Likert scale, and processed using SmartPLS software. The results show that work discipline has a positive effect on performance, teamwork has a positive effect on performance, work discipline positively affects work motivation, teamwork positively affects work motivation, and performance positively affects work motivation. Additionally, work motivation mediates the relationship between work discipline and performance, as well as between teamwork and performance. Therefore, improving work discipline and teamwork, supported by high worl motivation, can enhance the performance of firefighters.